Sabia (Their beliefs and role civilization) - Jouni, wafa; Jnaidi , GHifar (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The Sabia, though they are a minority sect, has played a notable and role in the development of spiritual and intellectual life in Mesopotamia during rise of Christianity and Islam. Though they have undergone persecution in different eras, and humiliation that blocked them through ages, they proved to be an active people and joined social life actively in a way that surpassed their real economic and population weight. Their successors proved to be worth being the grand children of a well-educated group of Mandaes who showed keenness in the different cultural and scientific files in the Abbasids Period. In this research, those people are introduced and their role in civilization, their beliefs, their taboos, and their scientific superiority and enriching civilization all over eras.